2022
DOI: 10.1097/md.0000000000031662
|View full text |Cite
|
Sign up to set email alerts
|

Application of family-involved smart medication management system in rural-dwelling middle-aged and older adult participants with chronic diseases: Management of chronic diseases in rural areas

Abstract: Management of patients with chronic diseases in rural areas and the use of medications need to be urgently addressed. Therefore, this study aimed to evaluate the efficacy of a family-involved smart medication management system for rural patients with chronic diseases. Between June and August 2021, 82 patients with chronic diseases were selected using convenience sampling from 2 county towns in Hebei Province, China. They were randomly divided into control (41 participants) and experimental (41 participants) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These studies involved a total of 3804 participants, divided into intervention (n=1937) and control (n=1867) groups. The intervention types were as follows: 4 studies used app interventions [ 38 - 41 ], 4 used telephone support [ 42 - 44 ], 4 used telemonitoring interventions [ 34 - 37 ], 6 used SMS text messaging interventions [ 45 - 50 ], and 4 used combined interventions [ 51 - 54 ]. Participants ranged in age from 35 to 80 years, with 51.3% being female.…”
Section: Resultsmentioning
confidence: 99%
“…These studies involved a total of 3804 participants, divided into intervention (n=1937) and control (n=1867) groups. The intervention types were as follows: 4 studies used app interventions [ 38 - 41 ], 4 used telephone support [ 42 - 44 ], 4 used telemonitoring interventions [ 34 - 37 ], 6 used SMS text messaging interventions [ 45 - 50 ], and 4 used combined interventions [ 51 - 54 ]. Participants ranged in age from 35 to 80 years, with 51.3% being female.…”
Section: Resultsmentioning
confidence: 99%
“…Non-adherence to medications or discrepancies between prescribed and digested medications is prevalent among older adults and can lead to treatment failure, and a multidisciplinary approach is recommended to optimize medication management [ 7 ]. He [ 32 ] built a multidisciplinary team and found that a family-involved smart medication management system could effectively improve medication adherence, self-efficacy in medication use, medication knowledge assessment scores, and family support for older adults. Interventions helping older people to anticipate and respond to medication-related problems may reduce the risk of harm associated with polypharmacy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%